Morphology Control in 2D Carbon Nitrides: Impact of Particle Size on Optoelectronic Properties and Photocatalysis. (7th May 2021) - Kröger, Julia; Jiménez‐Solano, Alberto; Savasci, Gökcen; Lau, Vincent W. h.; Duppel, Viola; Moudrakovski, Igor; Küster, Kathrin; Scholz, Tanja; Gouder, Andreas; Schreiber, Marie‐Luise; Podjaski, Filip; Ochsenfeld, Christian; et al.
Abstract: The carbon nitride poly(heptazine imide), PHI, has recently emerged as a powerful 2D carbon nitride photocatalyst with intriguing charge storing ability. Yet, insights into how morphology, particle size, and defects influence its photophysical properties are virtually absent. Here, ultrasonication is used to systematically tune the particle size as well as concentration of surface functional groups and study their impact. Enhanced photocatalytic activity correlates with an optimal amount of those defects that create shallow trap states in the optical band gap, promoting charge percolation, as evidenced by time‐resolved photoluminescence spectroscopy, charge transport studies, and quantum‐chemical calculations. Excessive amounts of terminal defects can act as recombination centers and hence, decrease the photocatalytic activity for hydrogen evolution. Re‐agglomeration of small particles can, however, partially restore the photocatalytic activity. The type and amount of trap states at the surface can also influence the deposition of the co‐catalyst Pt, which is used in hydrogen evolution experiments. Optimized conditions entail improved Pt distribution, as well as enhanced wettability and colloidal stability. A description of the interplay between these effects is provided to obtain a holistic picture of the size–property–activity relationship in nanoparticulate PHI‐type carbon nitrides that can likely be generalized to related photocatalytic systems. Abstract : Tuning the particle size of the 2D carbon nitride poly(heptazine imide) enables optimization of photocatalytic hydrogen evolution. It is shown that changes in the particle size affect the overall photocatalytic process in different ways, and the individual contributions of size‐related variables on the photocatalytic activity are traced back. This multi‐parameter analysis offers design strategies for next generation polymer photocatalysts.